Relationship between non-performing loans with interest rate and inflations/ Wardiyyah Ahmad - Ahmad, Wardiyyah (Faculty of Business and Management, 2010)
The purpose of this paper is to build various models to forecast non-performing loans in the banking sector of Malaysia. Given its association with bank failure and financial crises, the evaluation of non-performing loans is of great importance, and should therefore be of interest to developing countries. Using the estimates from these forecasting techniques, the performance of each model is evaluated to determine which performs best, as well as to facilitate comparison, and discussion of results. Given the forecasting models, the paper is capable of providing insights into the stability of the financial system and is also practical for commercial banks and bank regulators in terms of developing plans to regulate the occurrence of non-performing loans in the future. . In order to achieve this objective, the Vector Error Correction Model (VECM) is employed to determine whether interest rate and inflation rate affect the non-performing loans based on 48 monthly data.